Estudo de metodologia e técnicas para execução de ensaios de resposta em freqüência em transformadores de potência - Daniel Carrijo Polonio Araujo (2009)
Due to the importance of the power transformer in the electrical system, the detection of incipient faults and the ability to assess the current state of equipment become necessary, thereby avoiding losses from its unavailability. In this context, the non-invasive diagnostic techniques are very attractive because it helps to reduce the maintenance time.Faults diagnosis method in transformers by Frequency Response Analysis is a non-invasive test of great potential for use but it still needs more detail about procedures of results measurement and analysis. This dissertation presents a critical approach about theoretical and practical aspects related to the method application, and identifies characteristics and behaviors essential to the success of the test.Starting from theoretical and experimental researches, a consistent and robust methodology is proposed, incorporating some degree of immunity to spurious measurement factors and providing support for the correct interpretation of results. The sensitivity of tests using the methodology is evaluated from experiments of laboratory induced failures. The proposed solutions support future tests by standardization, enabling high levels of repetition in the results.This dissertations final contribution is to propose a Frequency Response test technique which provides reliable measurements for the diagnoses and prognoses elaboration stage.